Revealing the Effect of Nickel Nanoparticles for Li Plating and Stripping Processes on Ni−Nx Doped Hollow Carbon Sphere. Issue 20 (24th August 2021) - Liu, Ting; Huang, Ying; Zhou, Shengqi; Wang, Runtong; Lei, Jie; Xu, Pan; Yuan, Ruming; Dong, Quanfeng; Chen, Jiajia
Abstract: In this work, the effects of the coexistence of Ni−Nx sites and Ni metal nanoparticles of Ni−N−C (nickel‐nitrogen‐carbon) materials on the thermodynamic Li nucleation overpotential ( η ) and kinetic exchange current density ( j 0 ) are systematically studied. Ni‐Nx sites guarantee reduced nucleation resistance on the hollow carbon sphere (HCS) host, while the low amount residual of Ni nanoparticles plays an adverse role. The Li nucleation overpotential was down to 10.6 mV and the exchange current density increased from 1.139 to 2.325 mA cm −2 when the residual Ni nanoparticles in the prepared Ni−N−C composite were removed. As a result, pure Ni‐Nx sites displayed an average CE of 98.4 % over 300 cycles and a stable Li plating/stripping behavior for over 800 h. Abstract : By removing the residual nickel nanoparticles in the metal‐nitrogen‐carbon (M−N−C) composites, the pure metal‐nitrogen‐carbon Li hosts display a stable Li plating/stripping with an average CE of 98.4 % over 300 cycles.